(untitled) (KULT_online, 2025)
The special exhibition sponsored by the Ministry of Culture and Science of North Rhine-Westphalia, "Leben mit dem Tod. Über Abschied, Tod und Trauer" traces the developments and changes in Christian burial culture over the last 300 years with a special focus on the regional context. This is accompanied by the visualization of forms of farewell and mourning.